Adaptive nonlinear observer–based sliding mode control of robotic manipulator for handling an unknown payload. (March 2021) - Li, Guiying; Wang, Shuyang; Yu, Zhigang
This article presents the control synthesis of robotic manipulators with an unknown constant payload. A novel nonlinear disturbance observer with an adaptive scheme is designed to estimate the external force induced by the unknown constant payload. A general design procedure for designing the gain of the nonlinear observer is developed rather than the time-consuming trials and error to choose proper gain. The nonlinear observer gain is designed using an adaptive technique to extend the applicability of the disturbance observer. The stability of the proposed observer is established using Lyapunov method under certain conditions. The proposed nonlinear disturbance observer will be integrated with the sliding mode control to substantially alleviate the chattering problem. Also, simulation results are presented to verify the effectiveness of the proposed methods.